Lck regulates Vav activation of members of the Rho family of GTPases. - Han, J (1997)
Vav is a member of a family of oncogene proteins that share an approximately 250-amino-acid motif called a Dbl homology domain. Paradoxically, Dbl itself and other proteins containing a Dbl domain catalyze GTP-GDP exchange for Rho family proteins, whereas Vav has been reported to catalyze GTP-GDP exchange for Ras proteins. We present Saccharomyces cerevisiae genetic data, in vitro biochemical data, and animal cell biological data indicating that Vav is a guanine nucleotide exchange factor for Rho-related proteins, but in similar genetic and biochemical experiments we fail to find evidence that Vav is a guanine nucleotide exchange factor for Ras. Further, we present data indicating that the Lck kinase activates the guanine nucleotide exchange factor and transforming activity of Vav.